The Effect of Extract Papaya (Carica papaya) Seed on Aedes aegypti Larvae Mortality - Nur Wahid; Delima Engga Maretha; Asnilawati Asnilawati (Indonesian Journal of Biology Education, 2022)
Papaya plant is a plant originating from America with the scientific name Carica papaya. Papaya seeds contain flavonoids, glucotropaeolin, and phosphatidyl choline. Flavonoids are chemical compounds that have insecticidal properties. Flavonoids attack the nerves in several vital organs of insects, causing a weakening of the nerves, such as breathing and causing death. This study aims to examine the effect of papaya seed extract (Carica papaya) on the mortality of Aedes aegypti mosquito larvae and to determine the minimum inhibitory concentration of papaya (Carica papaya) seed extract required against Aedes aegypti mosquito larvae. The Aedes aegypti mosquito has a complete metamorphosis, and when it is in the larval stage, the Aedes aegypti mosquito has 4 phases, namely instar I, instar II, instar III, and instar IV larvae. The larvae used in this study were the larvae of the third instar Aedes aegypti mosquito. The research method used is a laboratory experimental method using a completely randomized design (CRD) where there are 4 treatments and 3 repetitions. The concentrations used in this study were 1 positive control, 10 ml, 30 ml, and 50 ml. The results were analyzed by One way ANOVA test followed by Post-Hoc LSD analysis. The results of the research that has been carried out show that the papaya seed extract (Carica papaya) which kills the most Aedes aegypti mosquito larvae is at a concentration of 50 ml, where in the first and second tests succeeded in killing 4 out of 5 larvae. In the last iteration managed to kill 5 out of 5 larvae. And it can also be seen that the minimum inhibitory concentration is at a concentration of 10 ml, where in 3 repetitions it can only kill 2 to 3 larvae from a total of 5 larvae. The 50 ml concentration is also the concentration that has the fastest effect, where on the fifth spray alone, there are already dead mosquitoes. While at a concentration of 10 ml, it takes a longer time, namely the seventh spray.